2007
DOI: 10.1590/1983-21172007090102
|View full text |Cite
|
Sign up to set email alerts
|

A Experiência De Um Grupo De Professores Envolvendo Ensino De Química E Informática

Abstract: ResumoEste trabalho teve como objetivo investigar a inserção da informática como estratégia didática para o ensino de Química. Por meio de encontros de um grupo de professores dessa disciplina, foram discutidas experiências já vivenciadas por eles sobre este tema, análise e exploração de softwares, além da elaboração e aplicação de uma proposta de aula na Sala Ambiente de Informática das escolas em que atuavam. Ficou evidente, nesse estudo, a importância de um espaço para o professor discutir sua prática profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Other authors on previous research addressed the question of whether the lessons with simulations or virtual labs had the same efficiency on student learning than lessons in real laboratories, and these studies have shown that both methods resulted in improvement of students' knowledge with no significant differences in the acquisition of scientific concepts [13,14]. These virtual environments are promising in improving school performance, ensure greater involvement and development of abilities such as investigation, critical thinking, use of technology and communication [15]. The integration of ICT into teaching methods benefits not only the students, but also provides cumulative development of competencies in the teachers who use it [16].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors on previous research addressed the question of whether the lessons with simulations or virtual labs had the same efficiency on student learning than lessons in real laboratories, and these studies have shown that both methods resulted in improvement of students' knowledge with no significant differences in the acquisition of scientific concepts [13,14]. These virtual environments are promising in improving school performance, ensure greater involvement and development of abilities such as investigation, critical thinking, use of technology and communication [15]. The integration of ICT into teaching methods benefits not only the students, but also provides cumulative development of competencies in the teachers who use it [16].…”
Section: Introductionmentioning
confidence: 99%